2015
DOI: 10.4194/1303-2712-v15_2_32
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ornamental fish breeding and growing are an important sector of aquaculture, which has increased income and occupations in the country in recent years. Presenting the new methods and producing the new food supplements could have effects on efficiency and sustainable development in this new technology. In the present study, the effect of ethanolic extract of F. vulgar having phytoestrogenic compounds on growth performance and fertility rate and gonadal tissue changes of guppy was tested for offering it as a foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Thus, it is essential to use the phytoestrogens such as the Vitex agnus-castus extract before the beginning of the reproduction season. Findings in the present study are consistent with the findings of Nazari and Roozbehani (2015) [41]. Their research on Poecilia reticulata indicates that Fennel Foeniculum vulgar extract influenced by the maturity of the ovum in a shorter time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, it is essential to use the phytoestrogens such as the Vitex agnus-castus extract before the beginning of the reproduction season. Findings in the present study are consistent with the findings of Nazari and Roozbehani (2015) [41]. Their research on Poecilia reticulata indicates that Fennel Foeniculum vulgar extract influenced by the maturity of the ovum in a shorter time.…”
Section: Discussionsupporting
confidence: 93%
“…Nazari and Roozbehani (2015) [41] described that Guppy larvae (Poecilia reticulata) were positively affected by phytoestrogens. The larvae attained the best enactment and displayed the fastest development of gonad using the herbal extract.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, according to Kesbic et al [29], the administration of a Monterey Cypress (Cupressus macrocarpa hartw) leaf essential oil as a dietary supplement of C. carpio's diet was found to be a suitable growth promotor. Moreover, similar results to our findings were obtained in the treatment of Oreochromis niloticus and Poecilia reticulate with fennel [17,30]. Studies have shown that a Bergamot (Citrus bergamia) peel oil supplementation in fish diets was able to optimize growth performance, feed utilization, and general health status [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Notably, fennel acetone extract shows promise in menstrual cycle regulation [14], and it may affect hormone levels by increasing the follicle-stimulating hormone while decreasing the luteinizing hormone and testosterone [15]. Moreover, fennel essential oils notably influence oocyte maturation and sexual maturity in fishes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Increased fertility rate (101) Moreover, Ivanov et al (69) showed that the Agastache foeniculum composed of 93.45% estragole produced a MIC of 1.25 L/ml on the growth of S. aureus (ATCC 25923) and other gram-positive bacteria. Estragole, the main volatile ingredient in A. rugosa essential oils, may be responsible for their phytotoxic and antibacterial properties (70).…”
Section: Guppymentioning
confidence: 99%